Molecular epidemiology of Enterobacter aerogenes acquisition: one-year prospective study in two intensive care units. - Davin-Regli, A (1996)
To evaluate the respective contributions of patient-to-patient transmission and endogenous acquisition of Enterobacter aerogenes isolates, we conducted a prospective epidemiologic study in two intensive care units (ICUs) between May 1994 and April 1995. We collected a total of 185 E. aerogenes isolates: 130 from 51 patients in a surgical ICU (SICU), 45 from 26 patients in a medical ICU (MICU), and 10 from the environments in these two ICUs. All isolates were typed by random amplification of polymorphic DNA and enterobacterial repetitive intergenic consensus PCR. Among the 175 clinical isolate, we observed 40 different profiles by random amplification of polymorphic DNA and 36 different profiles by enterobacterial repetitive intergenic consensus PCR. We identified a ubiquitous and prevalent clone, corresponding to 58% of SICU and 41% of MICU clinical isolates. Three epidemiologically related strains were specific to each ICU and represented 17% of SICU and 24% of MICU clinical isolates; unique type strains represented 17 and 29% of SICU and MICU clinical isolates, respectively, and E. aerogenes strains which were spread to a limited degree and which were isolated less than five times during the 1-year study period represented 8 and 6% of SICU and MICU clinical isolates, respectively. Our results show that E. aerogenes is acquired in the ICU in three different ways: patient-to-patient spread of a prevalent or an epidemiologically related strain, acquisition de novo of a strain from patients' own flora, and acquisition of a nonendemic strain followed by occasional patient-to-patient transmission. The findings point out the importance of patient-to-patient transmission in E. aerogenes acquisition and suggest that changes in E. aerogenes ecology in the hospital have taken place during the past decade.